(untitled) (Journal of Economic Research & Business Administration, 2015)
In this article, the organization’s marketing activities as members of the management of the organization on the basis of its strategic planning process, as well as the attractiveness of the strategic management of and the reasons for and the benefits provided by its role in the creation of an effective business.